In vitro and in vivo antimicrobial activity of two α-helical cathelicidin peptides and of their synthetic analogs - Benincasa, Monica (Peptides, 2003)
Two α-helical antimicrobial peptides (BMAP-27 and -28) and four synthetic analogs were compared for in vitro and in vivo antimicrobial efficacy. All peptides proved active in vitro at micromolar concentrations against a range of clinical isolates, including antibiotic-resistant strains. BMAP-27 and two analogs were more effective towards Gram-negative, and BMAP-28 towards Gram-positive organisms. In addition, BMAP-28 provided some protection in vitro against human herpes simplex virus type 1 (HSV-1). The parent peptides and mBMAP-28 analog protected mice from lethal i.p. infections in an acute peritonitis model at peptide doses significantly lower than those toxic to the animals, suggesting a satisfactory therapeutic index.